2012
DOI: 10.1007/s00330-012-2641-9
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of adenomyomatosis of the gallbladder from early-stage, wall-thickening-type gallbladder cancer using high-resolution ultrasound

Abstract: This study showed that HRUS can be helpful for distinguishing adenomyomatosis from early-stage, wall-thickening-type GB cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 22 publications
0
45
0
2
Order By: Relevance
“…However, the irregular thickening of the outer gallbladder wall, irregularity and thickening of the innermost wall layer which indicates the mucosa, loss of multilayer pattern of the gallbladder wall, focal discontinuity and intralesional vascularity are extensively associated with cancer occurrence. 6 For visualization of Color Doppler twinkling artifacts (CDTAs) 1.8 MHz color Doppler frequency is more highly recommended. 7 MR imaging clearly demonstrates gallbladder wall thickening and reveals RAS as intramural lesions that are hyperintense on T2-weighted images, hypointense on T1-weighted images, and nonenhancing.…”
Section: Resultsmentioning
confidence: 99%
“…However, the irregular thickening of the outer gallbladder wall, irregularity and thickening of the innermost wall layer which indicates the mucosa, loss of multilayer pattern of the gallbladder wall, focal discontinuity and intralesional vascularity are extensively associated with cancer occurrence. 6 For visualization of Color Doppler twinkling artifacts (CDTAs) 1.8 MHz color Doppler frequency is more highly recommended. 7 MR imaging clearly demonstrates gallbladder wall thickening and reveals RAS as intramural lesions that are hyperintense on T2-weighted images, hypointense on T1-weighted images, and nonenhancing.…”
Section: Resultsmentioning
confidence: 99%
“…A major issue with adenomyomatosis of the gallbladder is differentiating it from gallbladder cancer (27). Our previous study has already reported that IPMN was negative on DWBIBS/T2 (28).…”
Section: Discussionmentioning
confidence: 98%
“…4 In equivocal sonographic cases of adenomyomatosis, CT and MRI may help to differentiate. 4 In equivocal sonographic cases of adenomyomatosis, CT and MRI may help to differentiate.…”
Section: Discussionmentioning
confidence: 99%